STUDI ISLAM DALAM PENDEKATAN HISTORIS: (Studi Atas Tawaran Pemikiran Ibrahim M. Abu Rabi') - Minhaji Minhaji; Luluk Maktumah (LP2M Universitas Ibrahimy, 2013)
View of the west against the Islamic world to be changed. Islamic doctrine justified as violence, intolerance, terrorism, and the threat to Western society and the world global terms. It happened after the WTC bombing March 11, 2001. The meaning of Islam shifted from teaching about the principles of peace become violent theology, Islam is seen as monolithic, partial, incomplete. It was also made clear by